Strigolactones optimise plant water usage by modulating vessel formation - Zhao, Jiao; Shi, Dongbo; Kaeufer, Kiara; Song, Changzheng; Both, Dominik; Thier, Anna Lea; Cao, Hui; Lassen, Linus; Xu, Xiaocai; Hamamura, Yuki; Luzzietti, Laura; Bennett, Tom; et al. (Nature Communications, 2025)
Wood formation is crucial for plant growth, enabling water and nutrient transport through vessel elements, derived from cambium stem cells (CSCs). CSCs produce vascular cell types in a bidirectional manner, but their regulation and cell fate trajectories remain unclear. Here, using single-cell transcriptome analysis in Arabidopsis thaliana, we reveal that the strigolactone (SL) signalling pathway negatively regulates vessel element formation, impacting plant water usage. While SL signalling is generally active in differentiating vascular tissues, it is low in developing vessels and CSCs, where it modulates cell fate decisions and drought response. SL-dependent changes in vessel element formation directly affect transpiration rates via stomata, underscoring the importance of vascular tissue composition in water balance. Our findings demonstrate the role of structural alignment in water-transport tissues under unstable water conditions, offering insights for enhancing drought resistance in plants through long-term modulation of vascular development.
Gesehen am 06.11.2025